Decision Making in Uncertain Rural Scenarios by means of Fuzzy TOPSIS Method. (28th September 2011) - Armero, Eva; García-Cascales, M. Socorro; Gómez-López, M. Dolores; Lamata, M. Teresa
Abstract : A great deal of uncertain information which is difficult to quantify is taken into account by farmers and experts in the enterprise when making decisions. We are interested in the problems of the implementation of a rabbit-breeding farm. One of the first decisions to be taken refers to the design or type of structure for housing the animals, which is determined by the level of environmental control sought to be maintained in its interior. A farmer was consulted, and his answers were incorporated into the analysis, by means of the fuzzy TOPSIS methodology. The main purpose of this paper is to study the problem by means of the fuzzy TOPSIS method as multicriteria decision making, when the information was given in linguistic terms.